2003
DOI: 10.1038/sj.ijir.3901059
|View full text |Cite
|
Sign up to set email alerts
|

Role of some vasoactive mediators in patients with erectile dysfunction: their relationship with angiotensin-converting enzyme and growth hormone

Abstract: The imbalance between vasoconstrictors and vasodilators may play an important role in the pathogenesis of erectile dysfunction (ED). A total of 36 patients with ED, organogenic [diabetic (n ¼ 12) and nondiabetic (n ¼ 12)] and psychogenic (n ¼ 12) etiology, and 12 healthy adult men as controls were included. The levels of endothelin-1 (ET-1), growth hormone (GH), angiotensinconverting enzyme activity (ACE), nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) were determined in the flaccid penis cavernos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Accordingly, a high prevalence of erectile dysfunction (ED) is observed among hypertensive men (Lewis 2004;Muller and Mulhall 2006), and ET-1 is considered one of the best independent predictors for ED (Bocchio et al 2004). In addition, greater plasma levels of ET-1 were reported in the venous blood of patients with organic and psychogenic ED, but not in that of non-ED controls (Hamed et al 2003;El Melegy et al 2005). Furthermore, because ET-1 increases contractile responses to other vasoactive agents, one may speculate that increased contractions to EFS and phenylephrine are due to ET-1 effects.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, a high prevalence of erectile dysfunction (ED) is observed among hypertensive men (Lewis 2004;Muller and Mulhall 2006), and ET-1 is considered one of the best independent predictors for ED (Bocchio et al 2004). In addition, greater plasma levels of ET-1 were reported in the venous blood of patients with organic and psychogenic ED, but not in that of non-ED controls (Hamed et al 2003;El Melegy et al 2005). Furthermore, because ET-1 increases contractile responses to other vasoactive agents, one may speculate that increased contractions to EFS and phenylephrine are due to ET-1 effects.…”
Section: Discussionmentioning
confidence: 98%
“…25,26 In this study, we found a significant decrease of cavernosal and peripheral NO in diabetic patients, but not in patients with psychogenic ED, in agreement with others. 27 This finding could be due to the presence of advanced glycosylation end-products (AGEs), compounds that are formed as a result of non-enzymatic reaction between glucose and the amino groups of proteins. Advanced glycosylation end-products have been shown to quench NO and result in attenuation of NO-mediated relaxation of cavernosal smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…15 In ED patients, plasma levels of ET-1 are elevated, and are associated with reduction in growth hormone (GH), nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) in systematic and cavernous blood. 16 The vibration to perineal lesion from the saddle in motorcycle riding may cause peripheral nervous damage and the elevation of plasma levels of ET-1, and reduction in GH, NO and cGMP in the cavernous blood. Therefore, the vibration from motorbike may cause ED, and the degree of vibration to perineal lesion might be associated with the severity of ED.…”
Section: Discussionmentioning
confidence: 99%